A Novel Look at Peer Problems: Examining Predictors of Children's Sociometric Ratings of Classmates With ADHD Symptoms. (December 2022) - Mikami, Amori Yee; Na, Jennifer Jiwon; Ferrari, Mario A.; Owens, Julie Sarno
Research predominantly focuses on problematic behaviors in children with symptoms of attention-deficit/hyperactivity disorder (ADHD) to explain why they are disliked by their classroom peers. By contrast, the current study explores characteristics of peers that are associated with them disliking classmates with ADHD symptoms. To do so, we undertook a novel methodological approach using hierarchical linear modeling to examine the strength of the association between child characteristics, their sociometric ratings given to classmates, and the recipients' ADHD symptom levels. Participants were 194 children (Grades K–4) in 12 classrooms. Using the sociometric method, children rated their liking versus disliking of each classmate. Children's ADHD symptoms were reported by the teacher. Children's self-reported stigma about ADHD, their own sociometric ratings received, and teacher ratings of children's academic competence were collected. Results suggested that children who reported more stigma about ADHD, and who were more socially and academically competent, had a stronger negative association between the sociometric ratings they gave and the recipients' ADHD symptoms (i.e., were more likely to dislike classmates with ADHD symptoms). These effects were strongest at the end of the academic year relative to the beginning of the year. Implications for interventions targeting the peer group are discussed.